Application of Opposing Triangle Flaps in Three Different Kinds of Conjoined Twins. (November 2020) - Liu, Xiangqi; Li, Jun; He, Weijing; Zhang, Shuai; Dong, Chenbin
ABSTRACT: BACKGROUND: Conjoined twins are a rare congenital anomaly. If separation of the conjoined organs is feasible, reconstruction of the skin and tissue defects is a challenge for the plastic surgeon. This article describes the use of opposing triangle flaps in the separation of three different kinds of conjoined twins. METHODS: Plastic surgeons measured each conjoined area and designated the vertical length as a and the width as b . The length of the base of the opposing triangle flap was calculated to match a, and the height of the triangle to match b . RESULTS: After detailed calculations and careful surgery, the area of the opposing triangle flaps nearly covered the areas exposed after separation, and the three conjoined twins achieved primary closure of their wounds. The pygopagus and ischiopagus twins recovered uneventfully. The omphalopagus twins developed a wound infection, but after daily wound care, the twins recovered within a week. CONCLUSIONS: With precise calculations, the opposing triangle flap is a feasible and effective method for defect closure after separation of conjoined twins in certain cases. Clinicians may prefer this technique because it avoids the complications and second surgery necessitated by tissue expanders.